PENGARUH INSEKTISIDA MIKROBA Bacillus thuringiensis TERHADAP MORTALITAS Heliothis armigera PADA TONGKOL JAGUNG - Wiludjeng Widajati; Wiwin Windriyanti; Wahyu Santoso (Plumula : Berkala Ilmiah Agroteknologi, 2020)
Crop of corn (Zea mays L.) is seed crop which be used developed nations as staple food after rice. Pest activatir of cob of Heliothis armigera Hubner represents one of the corn crop pest which destroys many corn fruit especially at young fruit. The progress of technology has found a way to eradicate H. armigera biologically buy using a certain organism which is formulated in the form of pesticides. One of the product is Bactospeine WP which contains of active materials of Bacillus thuringiensis Berliner. The purpose of this research is to know the percentage of death symptom influenced by Bactospeine WP as stomach poison to some larva H. armigera at various given concentration. The research is conducted on laboratory. The research method used is Complete Random Device (CRD) with two factors and four times repetition. The first factor is concetration with three levels and second factor is larva instar with four levels. Perception is conducted on 1st, 2nd, 3rd, 4th and 5th day after treatment. Result of research indicates that death of larva H. armigera can be influenced by different of concetration of Bactospeine WP and instar larva.